Including 'difficult' students: counter politics, play and liveability in the primary school classroom. Issue 1 (2nd January 2022) - Teague, Laura
ABSTRACT: Drawing upon Judith Butler's conceptualisation of performativity and subjectification, this article explores the effects of different kinds of counter political action to disrupt exclusionary school practices that further marginalise children who are, often already, on the edges of school life. Firstly, tracing the impossibilities sometimes encountered when taking up a politics of reinscription, the article goes on to argue that the role of the pedagogue engaged in counter politics needs further disruption in order that children themselves have more space to determine who and how to be. Here, I explore how the rigid teacher/ student hierarchical binary can be unsettled through play. A more intersubjective relationship emerges between teacher and student which can make school feel more liveable and sustainable. Given the highly pressurised conditions in schools, globally, in this time of late neoliberalism, finding ways to make school more liveable is essential work. This article suggests that whilst moments of play, such as the one detailed here, are often fleeting, their effects can be felt afterwards. Finding opportunities for play is an important counter political strategy in schools at this time.